Pengaturan Jumlah Minimal Modal Dasar pada Pendirian Perseroan Terbatas - I Gusti Ayu Manik Maharani; Desak Gde Dwi Arini; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
In Article 33 of the Company Law, regarding the regulation of the capital of a PT, it is determined that at least 25% of the authorized capital in Article 32 of the Company Law must be issued and fully paid. This study aims to determine the regulation of the minimum amount of authorized capital at the establishment of a PT and to find out the consequences of the legal position of a PT established with an amount of authorized capital that is less than the provisions in the Company Law. This study uses a normative legal research method with a statutory approach and legal concepts. The results of the study show that the arrangement of the authorized capital of PT in PP Number 29 of 2019 is contrary to Article 32 paragraph (1). Establishing a PT to obtain a legal entity is not enough by making the Articles of Association of a PT, but it must be submitted for approval to obtain legal entity status. The legal consequence is that PT which has an authorized capital amount is less than the provisions in the Company Law. PT does not have legal entity status because after the deed of establishment or the Articles of Association of the PT has been completed, to obtain legal entity status one must submit an application to the Minister of Law and Human Rights for approval. Through this research, it is hoped that the government will immediately conduct an assessment and evaluation of laws and regulations, especially in the field of corporate law